2015
DOI: 10.1039/c4fo00680a
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of cinnamon (C. zeylanicum and C. cassia) extracts – identification of E-cinnamaldehyde and o-methoxy cinnamaldehyde as the most potent bioactive compounds

Abstract: Chronic inflammation is a contributing factor in many age-related diseases. In a previous study, we have shown that Sri Lankan cinnamon (C. zeylanicum) was one of the most potent anti-inflammatory foods out of 115 foods tested. However, knowledge about the exact nature of the anti-inflammatory compounds and their distribution in the two major cinnamon species used for human consumption is limited. The aim of this investigation was to determine the anti-inflammatory activity of C. zeylanicum and C. cassia and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 26 publications
(48 reference statements)
3
67
0
2
Order By: Relevance
“…RAW 264.7 cells were plated at 2.5 × 10 5 cells/mL in 24 well-plates and then incubated with or without LPS (1 µg/mL) in the absence or presence of various concentrations of samples for 24 h. One hundred microlitres of cell culture medium were mixed with 100 µL of Griess reagent (equal volumes of 1% sulphanilamide in 5% phosphoric acid and 0.1% N-1-naphtylethylenediamine dihydrochloride in distilled water), incubated at room temperature for 10 min, and then the absorbance at 540 nm was measured in a microplate reader. Nitrite concentrations in the supernatants were determined by comparison with a sodium nitrite standard curve (Gunawardena et al, 2015;Hooshmand et al, 2015). Fresh culture medium was used as the blank in all experiments.…”
Section: Nitric Oxide Assaymentioning
confidence: 99%
“…RAW 264.7 cells were plated at 2.5 × 10 5 cells/mL in 24 well-plates and then incubated with or without LPS (1 µg/mL) in the absence or presence of various concentrations of samples for 24 h. One hundred microlitres of cell culture medium were mixed with 100 µL of Griess reagent (equal volumes of 1% sulphanilamide in 5% phosphoric acid and 0.1% N-1-naphtylethylenediamine dihydrochloride in distilled water), incubated at room temperature for 10 min, and then the absorbance at 540 nm was measured in a microplate reader. Nitrite concentrations in the supernatants were determined by comparison with a sodium nitrite standard curve (Gunawardena et al, 2015;Hooshmand et al, 2015). Fresh culture medium was used as the blank in all experiments.…”
Section: Nitric Oxide Assaymentioning
confidence: 99%
“…NSAIDs in particular can cause severe side effects, most importantly gastric ulcers. NSAIDs are specifically designed as inhibitors of cyclooxygenase (COX) enzymes and, in contrast to CSAIDs, do not influence the production of proinflammatory cytokines such as TNF- α or free radicals such as nitric oxide [28]. CSAIDs specifically target p38 MAPK and NF- κ B signalling pathways to inhibit cytokine-mediated events with demonstrated efficacy in a range of animal models [29, 30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, pharmacological compounds with the ability to attenuate the production of these inflammatory molecules may have potential for the treatment of many inflammatory diseases including AD [21, 22, 28, 34, 35]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that cinnamon has lipid-lowering activity [37] and may also reduce insulin resistance [38]. It also has anti-inflammatory properties [39]. …”
Section: Combination Of Food Substancesmentioning
confidence: 99%